Forty-five years of law and literature: reflections on James Boyd White's The Legal Imagination and its impact on law and humanities scholarship. Issue 1 (2nd January 2019) - Gurnham, David; Mertz, Elizabeth; Burns, Robert P.; Anderson, Matthew; Sammons, Jack L.; Eisele, Thomas D.; Berger, Linda L.; Meyer, Linda Ross
ABSTRACT: This special section of Law and Humanities focuses on the 45th anniversary edition of James Boyd White's The Legal Imagination : a book that was ground-breaking when it first appeared in 1973 (since it is generally credited as having initiated the 'law and literature' movement) and that remains a hugely important resource today. White's approach to legal scholarship and education - reading law's instruments, its rhetoric and concepts alongside, above, below and in-between literary works and criticism - opened up a new world of intellectual possibilities. Realization of these possibilities has come in the form of the growth and flourishing, not only of law and literature but also numerous other intersections of law and the humanities that owe a debt to White. This symposium brings together seven eminent scholars (and readers of The Legal Imagination ) to reflect on the contribution that White's book made and continues to make to law and humanities education and scholarship. In the order that their essays appear, the authors for this symposium are Elizabeth Mertz, Robert P. Burns, Matthew Anderson, Jack L. Sammons, Thomas D. Eisele, Linda L. Berger and Linda Ross Meyer.